Tear Sample Analysis For SARS-COV-2 of Confirmed Cases of COVID-19 - Rai, Ashesh; Shrestha, S; Sharma, D; Prasai, G; Mishra, BK; Bhatt, CP (Nepal Medical College Journal, 2021)
Researchers in 2004 found that tear flim can be one of the modes of transmission of SARS-CoV. Considering the fact that SARS-CoV-2 is similar to SARS-CoV, it is speculated that there may be a risk of transmission through tear flim in patients with COVID-19. Therefore, this study was conducted to understand whether COVID-19 viral genome is present in the tear film or not. It was a cross-sectional quantitative study done in Kathmandu Medical College Teaching Hospital, Duwakot. Tear sample collection was done using schirmer’s strip and conjunctival swab of confirmed COVID-19 positive admitted cases and then the sample was sent for viral genome analysis. Especially designed proforma was used for recording the patient demographics, history, clinical examination findings and investigations results. Data were analyzed using the Statistical Package for the Social Sciences (version 21) and expressed in frequency, percentage and mean. Out of 30 enrolled patients, 23.3% (n=7) showed positive results in tear RT-PCR test for SARS-CoV-2. Among them, 85.7% (n=6) had positive tear sample RT-PCR on the very first day of sample collection with their CT value in tear sample ranging from 30-35. Patients who were positive were mostly in the age group of 21-30 years (71.4%) and were local vendors by occupation (71.4%). However, none of the patients had any ocular symptoms. Tear sample analysis with RT-PCR showed 23.3% positivity for SARS-CoV-2. Early collection and analysis of tear sample can yield maximum positive results therefore tear film could be one of the modes of transmission of SARS-CoV-2 virus.